Peran Wakil Talqin dalam Pengembangan Dakwah Tarekat - Opik Jamaludin (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2018)
Deputy talqin is a person who is trusted by the Sheikh of the murshid to give to anyone who wants and wants to practice the qodariyah naqsyabandiyah suryalaya (tqns) tarekat. Appointment of deputy talqin is the pro-creative rights of murshid teachers. Deputy talqin stands for the murshid teacher in various ways. Especially in terms of development of propaganda tqns. Deputy Talqin besides having a duty in the affairs of the tarekat, the representative of taqlin also has a role as a practicing, safeguarding and preservation of the tarekat teachings. The purpose of this study was to analyze the role of the representative talqin in the development of the TQNS missionary movement. Based on the results of the study it can be seen that the role of the representative talqin in the development of da'wah propaganda covers several aspects. The process of development through the field of education such as the founding of foundations, formed a da'wah organization. In the field of puppet art culture, the field of media is carried out through private television programs namely peaceful Indonesian on TV One. The practice of the teachings of the tarekat originating from the previous murshid reached the rosululloh peace be upon him. Like dzikir, khataman, mankiban, riaydoh and pilgrimage. Safeguarding the teaching of tqns through bookkeeping and filing. and preservation of tarekat teachings through introducing adherent teachings to the wider community. Among the successes of da'wah is that manakiban is followed by thousands of worshipers, the establishment of madrassas as a means of tqns. Overcoming juvenile delinquency. AbstrakWakil talqin adalah orang yang dipercaya oleh syekh mursyid untuk memberikan kepada siapa saja yang mau dan ingin mengamalkan tarekat qodariyah naqsyabandiyah suryalaya (tqns). Pengangkatan wakil talqin merupakan hak progreatif guru mursyid. Wakil talqin kepanjangan tangan dari guru mursyid dalam berbagai hal. Terutama dalam hal pengembanagn dakwah tqns. Wakil talqin selain mempunyai tugas dalam urusan tarekat, wakil taqlin juga mempunyai peran sebagai pengamal, pengaman dan pelestarian ajarana tarekat. Tujuan penelitian ini adalah menganalisa tentang peran wakil talqin dalam pengembangan gerakan dakwah TQNS. Berdasarkan hasil penelitian dapat diketahui bahwa peran wakil talqin dalam pengembangan dakwah tqns meliputi beberapa aspek. Proses perkembangan melalui bidang pendidikan seperti pendirian yayasan, membentuk organisasi dakwah. Bidang kebudayaan seni wayang ajen, bidang media dilakukan melalui acara televisi swasta yaitu damai indonesiaku di tv one. Pengamalan ajaran tarekat yang bersumber dari mursyid sebelumnya sampai kepada rosululloh saw. Seperti dzikir, khataman, mankiban, riaydoh dan ziarah. Pengamanan ajaran tqns melalui pembukuan dan pengarsipan. dan pelestarian ajaran tarekat melalu mengenalkan ajaran atrekat kepada masyarakat luas. diantara keberhasilan dakwah adalah manakiban diikuti oleh ribuan jamaah, pendirian madrasah-madrasah sebagai sarana dalam tqns. Menanggulangi kenakalan remaja